Radiosensitivitas dan Heritabilitas Ketahanan terhadap Penyakit Antraknosa pada Tiga Populasi Cabai yang Diinduksi Iradiasi Sinar Gamma - ,, Nura; Syukur, Muhamad; Khumaida, Nurul; ,, Widodo (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTCommercial varieties of chili is still susceptible to anthracnose disease. Anthracnose is one of diseases which caused yield loss about 10-80% in rainy season and 2-35% in dry season. One of the disease control method is to develop new varieties resistant to anthracnose through gamma-ray irradiation. This research was aimed to determine radiosensitivity level and heritability of chili which generated by mutation inductions of three genotypes: IPB C2, IPB C10, and IPB C15. Seed of the three genotypes were irradiated by gamma rays at dosages of 100, 200, 300, 400, 500, 600, 700, 800, 900 and 1,000 Gy. The LD50 in IPB C2, IPB C10, and IPB C15 were 317.9, 591.4, and 538.8 Gy, respectively. The character of IPB C2 mutants ranged between very susceptible to resistant against anthracnose disease, IPB C10 tended to very susceptible to highly resistant, and genotype IPB C15 tended to susceptible to highly resistant. Genotype IPB C2 had high level in heritability for disease resistance character, while medium level in heritability value was obtained on genotype IPB C10 and IPB C15.Keywords: genotype, LD50, mutant, mutation, seed